The role of herbivorous water birds in aquatic systems through interactions with aquatic macrophytes, with special reference to the Bewick’s Swan – Fennel Pondweed system - Marcel Klaassen; B Nolet (2007)
The role of aquatic macrophytes in stimulating biodiversity and maintaining clear waters is currently undisputed. The management of (eutrophic) shallow waters is therefore often directed at (re-)establishing macrophyte domination. In contrast, the role of water birds has long been considered of minor importance for the functioning of fresh water ecosystems. Indeed, in terms of biomass and production, water birds constitute only a minor part of these systems. However, water birds may graze heavily on water plants under certain circumstances, and the question arises whether herbivorous water birds have an important indirect effect on shallow fresh water systems. Mainly illustrated with the interaction between Bewick’s Swans and Fennel Pondweed, we present data on the role that water plants may play in the life of water birds and how water birds may impact water plants’ fitness in terms of survival, production, dispersal and competitive ability. It appears that water plants may be crucial for water birds during periods of high-energy requirements, such as migration. Despite the plants’ costs associated with water bird grazing, the interaction between water birds and water plants varies in nature from an apparent predator–prey relationship to a mutually beneficial interaction depending on the context and the perspective. For the case of the Bewick’s Swan–Fennel Pondweed interaction, regular bird grazing is sustainable and may actually favour the plant’s dispersal. Thus, Bewick’s Swans themselves may in fact play a crucial role in establishing and maintaining the Fennel Pondweed rich staging sites between the swans’ wintering and breeding grounds, which are vital for the swans’ successful migration.